A correction procedure for self-induced velocity of a finite-sized particle in two-way coupled Euler–Lagrange simulations. (February 2023) - Balachandar, S.; Liu, Kai
Abstract: The importance of incorporating a correction to undo the self-induced perturbation velocity of a particle, when its size becomes comparable to the Eulerian grid, in a two-way coupled Euler–Lagrange (EL) simulation is now well appreciated. The present work improves upon the prior correction procedures in a few important ways. First, the past correction procedures have been scalar-based with the assumption that the quasi-steady force is the source of self-induced velocity perturbation. Here we generalize to a vector correction procedure and thereby the directions of feedback force and relative velocity can be different. This allows the correction procedure to be used even in the presence of added-mass, history, and lift forces. Second, the effect of a nearby wall has been systematically included in the correction procedure. The correction procedure depends on fundamental Oseen solutions of streamwise and transverse regularized feedback forces. We present a Fourier transform-based analytical approach to obtaining these regularized Oseen solutions. We also present a step-by-step numerical procedure for obtaining the Oseen solutions in any EL code. With the analytical or numerical Oseen functions, the correction procedure can be easily implemented in any EL code. Iterations are required in solving the implicit correction equations and it is demonstrated that the correction procedure converges rapidly within three or four iterations. A simple empirical approach is also presented to account for unsteady effects in the correction procedure. Highlights: A self-induced velocity model for two-way coupled Euler–Lagrange simulations The vectorial model can account for forces more than the quasi-steady component. The model can account for inviscid nearby walls by superposing mirror images. The model is compatible with any two-way coupled filters and discretization schemes. Algorithmic steps on how to implement the self-induced velocity correction model.